PRODUK SAMPING TANAMAN UBIKAYU SEBAGAI POTENSI BIOEKONOMI UNTUK PERTANIAN MASA DEPAN - Fahrur Rozi; Quartina Pudjiastuti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2019)
Potential and opportunities for cassava development are still very broad along with development of companies in livestock, processed food, and other industries. Added value of cassava commodities resulting from development of downstream industries (processed products) is far higher than upstream industries (primary products), so that development paradigm in agriculture sector in future should be directed towards product expansion including its waste. This study aims to examine the economic value of cassava as a future crop from direct as well as by-products and their development strategies. Data was collected from small-scale tapioca flour farmers, ranchers and entrepreneurs. SWOT analysis was used to determine relevant development strategies. Analysis shows that cassava has an potential, especially as a raw material for food and feed industry. In short term, developing cassava strategy as an industrial raw material is to use new technologies i.e. varieties and cultivation techniques for planting arrangements. Cassava potential economic value is relatively high in terms of farming aspects, food raw materials, feed and industry. This potential, apart from main product, is also by-product that has been neglected at 29.7% of cassava main value. By-products potensial has not been used optimally and a bioeconomic value of biomass that can support integrated agriculture in the future.